“Complexo” Veryhachium: Acritarcos Indicativos do Siluriano? - Tereza Regina Machado Cardoso; Maria Antonieta da Conceição Rodrigues (Anuário do Instituto de Geociências, 2005)
Acritarchs are known to be related to cysts of marine microphytoplankton, and are reliable indicators of marine paleoenvironments. The acritarch genus Veryhachium was erected by Deunff (1954) to encompass an entire plexus of microfossils first recorded in Paleozoic strata of England and France. It includes a variety of organic-walled microphytoplanktonic organisms consisting of a smooth or granulated, hollow vesicle with triangular to polygonal shape. The vesicle is provided with up to eight, tapered and long, often bent, unbranched processes, which are hollow and present either smooth or granulated walls. The oldest known representatives of Veryhachium are from the Upper Cambrian, but the genus becomes most abundant and diversified in succeeding Paleozoic intervals. By contrast, post-Paleozoic records include only two species from the Cretaceous, and three Tertiary species which Stancliffe & Sarjeant (1994) regard as anomalous forms. The occurrence of Veryhachium in recent sediments of Bolivia has been attributed by several authors to the reworking of Paleozoic strata. Due to the long stratigraphic range of most of its species, the genus has generally played a secondary role in biostratigraphic zonations. Our palynological study of the Trombetas Group (Amazonas basin, northern Brazil), based on numerous outcrops and Eletronorte shallow coredrills, together with core samples of a single Petrobras well, has recorded such Silurian species as Veryhachium owensii, V. oklahomense, V. pertonense, V. longispinosu, V. rhomboidium and V. lairdii. They occur together with more age-diagnostic Silurian species belonging to the genera Deunffia and Domasia. The diversity of Veryhachium in the Trombetas Group highlights not only its importance as a paleoenvironmental indicator, but also its usefulness in characterizing regional palynomorphs assemblages in Paleozoic basins of Western Gondwana.